A Liege Town in Moravia of the 17th Century in Terms of Marriage Migration. Combined Testimony of Parish Registers and Marriage Contracts - Jan Dvořák (Theatrum Historiae)
This study is essentially aimed at solving of two sets of questions in connection with the episcopal town of Svitavy in the first decade of the 17th century. First, it attempts to reveal more general trends of the development of Moravian liege towns of the mentioned time period. It primarily focuses on the problem of contacts between town people and country background in the intentions of marriage strategies. The research assignment is to find out what intensity of entering into marriages was between town dwellers and villagers, and how important role, in this respect, the boundaries of a relevant domain or its internal circles played. The paper also deals with the problem of marriage immigration and emigration, and at the same time it tries to capture the prevailing model, taking into account the legal status of residential units, where the migration to the town came from and where, outside from the town, it was directed, and marital status of a groom and a bride, too. The second group of the questions is connected with the criticism of the basic input sources (registers and wedding contracts), their information potential and possibilities of their interpretation.